Economic Drivers of Consumer Price Growth in the EU–27 Service Industry during the Post‑pandemic Period - Mileris, Ričardas (Comparative Economic Research. Central and Eastern Europe, 2023)
The post‑pandemic period in the European Union is distinguished by the growth of business economic activity after two years of restrictions, growing debts and money supply, and extremely high inflation. This research analyses the Harmonised Index of Consumer Prices (HICP) in the service industries of the EU–27, comparing it to overall inflation and price growth in consumer goods markets. It also highlights the economic factors that contribute to the differences between service price growth in the EU–27. The results make it possible to classify the EU–27 countries according to the differences in service price changes. Consistent patterns of service HICP are highlighted, and the economic factors considering their relative importance to service HICP are ranked. Since 2022, public and governmental discussions concerning the post‑pandemic inflationary shock have become prevalent, so this research allows us to understand the economic factors that caused such huge inflation and substantiates the need for monetary policy measures to slow down inflation.